3.8 million blinded by cataract each year: projections from the first epidemiological study of incidence of cataract blindness in India. Issue 6 (June 1990) - Minassian, D C; Mehra, V
Abstract : Data from a population based longitudinal study of randomly selected communities in Central India have for the first time provided direct estimates of age specific incidence of blindness from cataract. Person-time denominators have been used to compute age specific incidence rates (risk) of blindness from cataract for populations aged 35 and older. These age specific incidence measures have been applied to the 'population at risk' in each 5-year age class in order to estimate the total number of new cases of cataract blindness that occur in the country each year. The findings indicate that an estimated 3.8 million persons become blind from cataract each year in India (approximate 95% confidence limits: 3 to 4.5 million). The reasons why the estimates are considered as minima, and their implications concerning future national planning of ophthalmic services, are briefly discussed.